2009
DOI: 10.4028/www.scientific.net/kem.421-422.301
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Rare Earth (Ln = Gd, Dy, Y and Yb) Doping on the Microstructure and Reliability in BaTiO<sub>3</sub>-Based Monolithic Ceramic Capacitors (MLCs)

Abstract: The effect of rare earth (Ln = Gd, Dy, Y and Yb) and Mg ions on the microstructure and reliability of BaTiO3-based monolithic ceramic capacitors (MLCs) with Ni electrodes was investigated. The X-ray diffraction results about the lattice volume of sintered specimens suggested that Gd and Dy ions predominatly substituted into the Ba-site, Yb ions gave exclusive substitution at the Ti-site, while Y ions occupied either the Ba- and Ti-site. The reliability of ceramic capacitors was increasing with increasing the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…[1][2][3][4][5][6][7] The Gd-and Mg-substituted barium titanate crystals (Ba 1−x Gd x )(Ti 1−x=2 Mg x=2 )O 3 were found as one of the suitable materials from the viewpoint of the dielectric properties and stability of ceramics. 8) Structure fluctuations of BaTiO 3 in the paraelectric cubic phase, especially the fluctuation of Ti ions, have also been discussed extensively in connection with the successive phase transition mechanism of BaTiO 3 . X-ray diffuse scattering, single crystal structure analyses, NMR measurements, X-ray laser speckle, and other studies suggested symmetry breaking above the ferroelectric phase transition temperature T C = 403 K. [9][10][11][12][13][14] A recent convergent-beam electron diffraction study successfully gave a direct evidence of the 〈111〉 offcentered Ti ion.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7] The Gd-and Mg-substituted barium titanate crystals (Ba 1−x Gd x )(Ti 1−x=2 Mg x=2 )O 3 were found as one of the suitable materials from the viewpoint of the dielectric properties and stability of ceramics. 8) Structure fluctuations of BaTiO 3 in the paraelectric cubic phase, especially the fluctuation of Ti ions, have also been discussed extensively in connection with the successive phase transition mechanism of BaTiO 3 . X-ray diffuse scattering, single crystal structure analyses, NMR measurements, X-ray laser speckle, and other studies suggested symmetry breaking above the ferroelectric phase transition temperature T C = 403 K. [9][10][11][12][13][14] A recent convergent-beam electron diffraction study successfully gave a direct evidence of the 〈111〉 offcentered Ti ion.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7] When the trivalent R and divalent Mg ions are substituted simultaneously for the Ba and Ti ions, respectively, solid solutions of the chemical formula (Ba 1−x R x )(Ti 1−x=2 Mg x=2 )O 3 are formed from the viewpoint of charge compensation. This atomic co-substitution improves the dielectric properties and stability of BaTiO 3 ceramics, 8) and at the same time reduces the ferroelectric phase transition temperature T C of BaTiO 3 with increasing Gd and Mg contents. The phase transition temperature of perovskite-type ABO 3 ferroelectrics including B metal ions with d 0 electronic configurations has often been discussed in connection with the B d-O 2p orbital hybridization.…”
Section: Introductionmentioning
confidence: 96%
“…We have recently revealed that Gd is the most effective rare-earth element R for suppressing insulation degradation for applied voltage and temperature stress among (Ba 0:94 R 0:06 )(Ti 0:97 Mg 0:03 )O 3 -based MLCCs. 7) High permittivity (>10000) at room temperature and high specific resistance (>10 10 Ám) can be achieved up to 400 K in (Ba 0:94 Gd 0:06 )(Ti 0:97 Mg 0:03 )O 3 .…”
Section: Introductionmentioning
confidence: 97%